2010
DOI: 10.1166/jnn.2010.2691
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Activities of Endohedral Metallofullerene Optimized for Nanopharmaceutics

Abstract: Endohedral metallofullerenes, a novel form of carbon-related nanomaterials, currently attract wide attention for their potential applications in biomedical fields such as therapeutic medicine. Most endohedral metallofullerenes are synthesized using C60 or higher molecular weight fullerenes because of the limited interior volume of fullerene. It is known that the encapsulated metal atom has strong electronic interactions with the carbon cage in metallofullerenes. Gd@C82 is one of the most important molecules in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 75 publications
0
21
0
Order By: Relevance
“…It has been suggested that Gd@C 82 (OH) 22 has potential both as diagnostic and as therapeutic agent [455]. The number of hydroxylic groups should be kept below 36; higher hydroxylated compounds easily form unstable opencaged structures, leading to release Gd 3+ ions in vivo [456].…”
Section: Fullerenesmentioning
confidence: 99%
“…It has been suggested that Gd@C 82 (OH) 22 has potential both as diagnostic and as therapeutic agent [455]. The number of hydroxylic groups should be kept below 36; higher hydroxylated compounds easily form unstable opencaged structures, leading to release Gd 3+ ions in vivo [456].…”
Section: Fullerenesmentioning
confidence: 99%
“…Numerous experiments have been conducted both in vitro and in vivo to examine the cytotoxicity of [Gd@C 82 (OH) 22 ] n . Previous experiments revealed that [Gd@C 82 (OH) 22 ] n particles have low toxicity to the growth of cells, such as hepatoma cells (HepG2), 9 human microvascular endothelial cells, 10 human breast cancer cells (MCF-7), 11,12 and human umbilical vein endothelial cells (ECV304), 11 among others. Similarly, several animal experiments with different cancer xenograft models suggest that [Gd@C 82 -(OH) 22 ] n particles possess very low toxicity in vivo .…”
Section: Low Toxicity Of [Gd@c82(oh)22]n Nanoparticlesmentioning
confidence: 99%
“…Those fullerenes that encapsulate metal atoms are called endohedral metallofullerenes. 23 Hydroxylation (attaching OH-groups) is the most common functionalization, which renders the molecule more hydrophilic, 24 but other polar adducts will also have the same effect. 25 …”
Section: Fullerenes As Photosensitizersmentioning
confidence: 99%